Hariyatie Soekarno : the hidden story : hari-hari bersama Bung Karno, 1963-1967. - Soekarno, Hariyatie; Soekarno, Haryatie (Jakarta : Gramedia Widiasarana Indonesia, 2001)
Autobiography of Hariyatie, as wife of Soekarno, the 1st president of Indonesia.
In Indonesian.
Keywords: Soekarno, Hariyatie; Presidents'spouses -- Indonesia -- Bibliogrphy